EVALUATION OF THE DESIGN OF RETAINING WALLS ON THE ROAD SUKABUMI (BAROS) - SAGARANTEN KM BDG 115+200 - Pasha, Muhammad Kemal; Suhendi, Cece; Saputri, Utamy Sukmayu (ASTONJADRO, 2022)
The Sukabumi (Baros) – Sagaranten Km Bdg 115+200 road section which is located in Sukabumi Regency is a road section for the province of West Java. Because the road is always damaged due to being eroded by water infiltration in the rice fields that seeps into the road body area at that location and the soil at that location tends to be unstable based on the results of lab tests having a shear angle value of 4.99áµ’ and having a specific gravity of 17.45, then it is carried out analysis of the existing damaged retaining wall and the design of a new gabion-type retaining wall at that location. The gabion retaining wall building will be designed with 3 designs, the first using a stone volume of 13 m3, the second using a stone volume of 8 m3 and the third using a stone volume of 6.5 m3. Based on the results of the calculation analysis using Rankine theory, it was found that the existing retaining wall was unable to withstand the shearing force which got a check value of 1.18 which should have a value of SF > 1.5, while the 3 gabion plan buildings got the appropriate SF value, namely against the overturning force, shear force and soil bearing capacity.